Extraction and physico-chemical characterization of a versatile biodegradable polysaccharide obrained from green algae - Alves, A. (2010)
During the last years, considerable attention has been given to different marine organisms, like algae, as potential sources of valuable materials. The continuous demand for novel materials and technologies is high and research on the underexploited marine green algae, including its polysaccharidic part—ulvan, has increased accordingly. In this research work, a novel method for extraction of ulvan from green algae is proposed and demonstrated successfully. Different characterization techniques were employed to characterize the isolated algal polysaccharide, namely, on what concerns its thermal trace and crystallinity. Upon heating, ulvan behaves as a non-meltable polysaccharide that is thermally stable before degradation at 220 C. Ulvan is semi-crystalline in nature and possesses high hygroscopic features, as revealed in this research work. Due to its properties, ulvan can be considered, pure or modified, as a versatile biodegradable polymer for different applications, including tissue engineering and regenerative medicine.